2007
DOI: 10.1007/s10164-007-0059-7
|View full text |Cite
|
Sign up to set email alerts
|

Within-group differences in captive Diana monkey (Cercopithecus diana diana) behaviour

Abstract: This case study examines the activity budgets of captive Diana monkeys (Cercopithecus diana diana) and discusses results in the context of what is known regarding captive and wild-type behaviour in this species and other guenons. The activities of a family group of Diana monkeys (two parents and four offspring) housed at Edinburgh Zoo, UK, were quantified using a 5-min interval scan sampling technique. The 5100 observation points collected showed that the subjects spent the largest proportion of their time obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 26 publications
3
8
0
Order By: Relevance
“…This corresponds to findings from numerous other studies (Davey, 2007). Specifically, activity increased with increased visitor numbers (Todd et al, 2007), visitor activity (Hosey and Druck, 1987;Mitchell et al, 1992) and visitor presence (Mallapur et al, 2005). However, this effect is not consistent across species; for example, western lowland gorillas significantly reduced foraging and feeding with increasing visitor numbers (Clark et al, 2012).…”
Section: Effect Of Visitor Numbersupporting
confidence: 85%
See 4 more Smart Citations
“…This corresponds to findings from numerous other studies (Davey, 2007). Specifically, activity increased with increased visitor numbers (Todd et al, 2007), visitor activity (Hosey and Druck, 1987;Mitchell et al, 1992) and visitor presence (Mallapur et al, 2005). However, this effect is not consistent across species; for example, western lowland gorillas significantly reduced foraging and feeding with increasing visitor numbers (Clark et al, 2012).…”
Section: Effect Of Visitor Numbersupporting
confidence: 85%
“…Some studies have found increases in auto-grooming similar to the current study, e.g. in western lowland gorillas grooming increased with visitor density (Wells, 2005), but in other species, such as Diana monkeys, grooming behaviours decreases with increased visitor numbers (Todd et al, 2007).…”
Section: Effect Of Visitor Numbersupporting
confidence: 84%
See 3 more Smart Citations